2021
DOI: 10.1002/smj.3362
|View full text |Cite
|
Sign up to set email alerts
|

On top of the game? The double‐edged sword of incorporating social features into freemium products

Abstract: Research Summary Freemium products require widespread diffusion for their success. One way to do this is by incorporating social features (e.g., multiplayer functionality, virtual collaboration, ridesharing), which can generate network effects and result in a product becoming a superstar. However, social features can be a double‐edged sword: When demand potential for freemium products is large, social features can significantly boost a product's appeal resulting in more adoption, more usage, and more in‐app pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…While these papers suggest that products which use freemium strategies benefit from network effects, this is not studied explicitly, particularly in relation to how it shapes market outcomes. One exception is a recent paper by Rietveld and Ploog (2021) who look explicitly at the choice to implement social media features which can strengthen network effects. They discuss explicitly the interplay between freemium strategies and direct network effects, and show how network effects may actually harm freemium products when the network (size of the user base that benefit) is small.…”
Section: Freemium Strategiesmentioning
confidence: 99%
“…While these papers suggest that products which use freemium strategies benefit from network effects, this is not studied explicitly, particularly in relation to how it shapes market outcomes. One exception is a recent paper by Rietveld and Ploog (2021) who look explicitly at the choice to implement social media features which can strengthen network effects. They discuss explicitly the interplay between freemium strategies and direct network effects, and show how network effects may actually harm freemium products when the network (size of the user base that benefit) is small.…”
Section: Freemium Strategiesmentioning
confidence: 99%
“…By focusing on the network effects present in the complementors' products, the study also contributes to the prior work that has brought attention to product-level network effects (Boudreau et al, 2021;Rietveld & Ploog, 2022;Shankar & Bayus, 2003). While the prior work has demonstrated that the network effects are heterogeneous across products in the same industry and how they can facilitate product adoption and performance, the findings from the article highlight that the efficacy of the product-level network effects can be contingent on the firm's resources and market characteristics.…”
Section: Discussionmentioning
confidence: 97%
“…It is because multiple products may be used concurrently but none of them might have enough users to create a valuable experience for the users. In the context of multiplayer games, multiple products in the same segment may coexist while each has an active online userbase that is insufficient to ensure a smooth playing experience (Rietveld & Ploog, 2022). 5 Further, lower quality products may end up dominating the market when temporary fluctuations in the number of users may be amplified into irreversible positions due to high switching costs.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations